A Bibliography of Publications in Economic and Social History Printed in Poland in 1997-2000 - Kowal, Ewelina (Studia Historiae Oeconomicae, 2006)
Bibliography Methodology, theory and history of economic thought Sources and source studies General publications Demography Social structure and mobility Labour, social movements and trade unions Social and economic relations in rural communities Towns and urbanization processes Industry, mining, handicraft and architecture Transport and communication Maritime economy, aquatic economy Trade Credit, finance, money and prices Insurance and social welfare Consumption